Efficient supercapacitor energy usage in mobile phones - Monteiro, J.; Garrido, N.; Fonseca, R. (IEEE International Conference on Consumer Electronics -Berlin (ICCE-Berlin), 2011)
This paper proposes a solution for using supercapacitors to power mobile phones. Based on a DC/DC voltage converter and a supercapacitor stacking scheme, this solution is designed to maximize the usable energy of the supercapacitors as well as the converter's performance, which is confirmed in simulation. A specific charging scheme for this design is also proposed and simulated, enabling fast and efficient charging of the mobile device.